Store-Operated Calcium Entry via STIM1 Contributes to MRGPRX2 Induced Mast Cell Functions - Christopher J. Occhiuto; Ananth K. Kammala; Canchai Yang; Rithvik Nellutla; Marco Garcia; Gregorio Gomez; Hariharan Subramanian (Frontiers in Immunology, 2020)
Mast cells are inflammatory immune cells that play an essential role in mediating allergic reactions in humans. It is well-known that mast cell activation is critically regulated by intracellular calcium ion (Ca2+) concentrations. MAS-related G-protein coupled receptor-X2 (MRGPRX2) is a G-protein coupled receptor (GPCR) expressed on mast cells that is activated by various ligands, including several FDA approved drugs; consequently, this receptor has been implicated in causing pseudo-allergic reactions in humans. MRGPRX2 activation leads to an increase in intracellular Ca2+ levels; however, the Ca2+ mobilizing mechanisms utilized by this receptor are largely unknown. Previous reports showed that store-operated Ca2+ entry (SOCE) via the calcium sensor, stromal interaction molecule 1 (STIM1), regulates mast cell response induced by the high-affinity IgE receptor (FcεRI). In this study, using complementary pharmacologic and genetic ablation approaches we demonstrate that SOCE through STIM1 promotes MRGPRX2-induced human mast cell response in vitro. Importantly, SOCE also critically modulates MrgprB2 (mouse ortholog of human MRGPRX2) dependent inflammation in in vivo mouse models of pseudo-allergy. Collectively, our data suggests that MRGPRX2/MrgprB2 activation of mast cells is dependent on SOCE via STIM1, and further characterization of the MRGPRX2-SOCE-STIM1 pathway will lead to the identification of novel targets for the treatment of pseudo-allergic reactions in humans.